Razvoj pripovedovanja zgodbe v zgodnjem otroštvu - Marjanovič Umek, Ljubica (Psihološka obzorja (Ljubljana), 2010)
Storytelling is an important aspect of child's language competence, which largely depends on her/his understanding and expression of a decontextualised content and develops rapidly in the period between the second and sixth year of life. The purpose of this study was to examine age differences in children's storytelling in the period between the third and sixth year of age. In addition, we considered the effect of gender on storytelling of children of different ages. The sample included 156 children aged from 3 to 6 years, who were divided into 3 age groups, namely children, aged 3, 4 and 5 years. Child's storytelling competence was assessed with the Little Glove Storytelling Test. Children's stories told by a standard set of illustrations were analyzed in terms of criteria, designed to assess the developmental level of the stories. The criteria refer to the words, included in the story, the grammatical structure and the content of the story. The obtained results suggested that several important changes in the development of storytelling occur within the period of early childhood. The 5-years-old children told longer stories with a more complex grammatical structure and a coherent content as the 3-years-old children. Children's achievements on the individual criteria for assessing the developmental level of the stories progressed relatively steadily through all three age groups. The results also showed that gender had no significant effect on the storytelling of children of different ages.
Keywords: pripovedovanje zgodb; child; otroci; zgodnje otroštvo; starostne razlike; razlike med spoloma